ANALISIS TINGKAT KEBUGARAN JASMANI ATLET KLUB BOLA VOLI PUTRI INDONESIA MUDA SRAGEN - Irgi Putra Afandi; Vera Septi Sistiasih (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2023)
The purpose of this study was to determine the level of physical fitness of the young Indonesian women's volleyball club athletes in Sragen. The population in this study were all athletes of the Indonesia Muda women's volleyball club in Sragen, totaling 65 athletes. The requirements for taking the sample were all athletes of the Indonesian Young women's volleyball club in Sragen aged 16-19 years, namely 27 athletes. The method used in this study is a survey method with data collection techniques using tests and measurements using the Indonesian Physical Fitness Test (TKJI). Based on the results of the research conducted, for the TKJI test (Running 60 Meters, Push Ups, Sit Ups and Jumping Upright) out of a total of 27 respondents who were included in the "Good" Physical Fitness category, only 1 person. Meanwhile, 25 people were in the category of "Moderate" Physical Fitness and 1 person was in the "Less" category. The condition of the physical fitness of the athletes of the Indonesian Young women's volleyball club in Sragen is not in good condition, so it is necessary to improve the portion or method of training. From the results of this study it is hoped that it can increase the intensity of training so that physical fitness improves even better and can be used as a study to analyze the Physical Fitness Level of Volleyball Club Athletes.